How powerful are Macroeconomic variables in the Stock market? The case of Ghana - Peprah-Yeboah, James (2016)
A thesis submitted to the Department of Economics, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for the award of an Msc Economics degree.